La excusa del juzgador rechazada, a la luz de la Resolución 08-2018 de la Corte Nacional de Justicia y el principio de imparcialidad. - Rivera Chiriboga, Emilia Pavlova (2025)
The research paper titled "The Rejected Excuse of the Judge, in Light of Resolution 08-2018 of the National Court of Justice and the Principle of Impartiality" aims to conduct a legal and doctrinal analysis of the legal figure of the excuse presented by the judge in light of Resolution 08-2018 of the National Court of Justice in order to determine any violation of the principle of impartiality. This research will examine the procedure the judge must follow in the event they are involved in any of the grounds established in Article 22 of the Organic General Code of Processes. It is important to note that while this regulation briefly outlines the procedure, due to legal gaps, the National Court of Justice has deemed it necessary to issue a resolution that details the procedure extensively. However, this resolution does not frame the principle of impartiality. In order to carry out this research, bibliographic review was used as the primary research method, with particular emphasis on case analysis, which allowed for studying in practice how excuse procedures are carried out. The results indicate that, despite judges being subject to one of the grounds for excuses, these requests are often rejected, resulting in the case remaining with the same judge, thus jeopardizing the principle of impartiality as well as legal certainty. Furthermore, we have concluded that while Resolution 08-2018 provides a defined procedure for judges presenting their excuse, it ultimately undermines the principle of impartiality.